Artificial Water Channels: Towards Biomimetic Membranes for Desalination - Huang, Li‐Bo; Di Vincenzo, Maria; Li, Yuhao; Barboiu, Mihail (Chemistry : a European journal, 2021)
Natural Aquaporin (AQP) channels are efficient water translocating proteins, rejecting ions. Inspired by this masterpiece of nature, Artificial Water Channels (AWCs) with controlled functional structures, can be potentially used to mimic the AQPs to a certain extent, offering flexible avenues toward biomimetic membranes for water purification. The objective of this paper is to trace the historical development and significant advancements of current reported AWCs. Meanwhile, we attempt to reveal important structural insights and supramolecular self‐assembly principles governing the selective water transport mechanisms, toward innovative AWC‐based biomimetic membranes for desalination. Desalination membranes: The prime objective of Artificial Water Channels (AWC) is to explore the naturally evolved water translocation pathways and assess the possibilities of using them as the basis for ‘engineered’ desalination processes of enhanced performance. This review proposes to find an easily scalable AWC approach that could be immediately applied to desalination systems to increase their energy efficiency.